Is This a Word for an Emotion? Considering a Set of English Data - Tisari , Heli (TALENTA, 2022)
There are many words that rather clearly denote emotions, such as the nouns anger, happiness, and sadness. However, some cases are not so clear. For example, if a person feels relaxed, the adjective can refer to a physiological as well as an emotional state. It may be even more difficult to decide if a word such as the noun fun or the adjective warm refers to an emotional state. In this paper, I will discuss a list of 86 words that I collected while annotating a set of British English texts. They consisted of people’s fond memories of the music of digital games, and I aimed to mark all words that referred to emotions. I made notes of words that I was uncertain about. Here, those words are considered in the light of two dictionaries, the Macmillan English Dictionary for Advanced Learners, and the Oxford English Dictionary online.